2014
DOI: 10.3390/md12010394
|View full text |Cite
|
Sign up to set email alerts
|

Dinophysis Toxins: Causative Organisms, Distribution and Fate in Shellfish

Abstract: Several Dinophysis species produce diarrhoetic toxins (okadaic acid and dinophysistoxins) and pectenotoxins, and cause gastointestinal illness, Diarrhetic Shellfish Poisoning (DSP), even at low cell densities (<103 cells·L−1). They are the main threat, in terms of days of harvesting bans, to aquaculture in Northern Japan, Chile, and Europe. Toxicity and toxin profiles are very variable, more between strains than species. The distribution of DSP events mirrors that of shellfish production areas that have implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
253
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(277 citation statements)
references
References 227 publications
3
253
1
8
Order By: Relevance
“…The dinoflagellate genus Dinophysis is considered as the only source of PTX in marine waters (Reguera et al, 2014). Several PTX analogs have been found in culture conditions, field water samples and shellfish (Domínguez et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dinoflagellate genus Dinophysis is considered as the only source of PTX in marine waters (Reguera et al, 2014). Several PTX analogs have been found in culture conditions, field water samples and shellfish (Domínguez et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A few hundred cells per liter are enough to generate intoxications in humans by consuming contaminated shellfish (Yasumoto et al, 1980). Up to date, dinoflagellate species of the genus Dinophysis have been recently recognized as the only known source of pectenotoxins (PTX), a large family of lipophilic toxins originally associated with the DSP toxin complex (Reguera et al, 2014). Toxicological studies indicate that PTX are not diarrheagenic after oral administration to laboratory rodents, but PTX-1 is highly hepatotoxic and the other analogs are assumed to have similar effects (Terao et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Argentine Sea, it is known to occur between 36°and 55°S (Balech 2002). But D. tripos has never been cited as the causative agent of DSP events when it was the only or the overwhelmingly dominant species of Dinophysis in the microphytoplankton (Reguera et al 2014). In contrast, Dinophysis acuminata has been identified as the causative agent of DSP in Southern Brazil (Proenc xa et al 2007) and, combined with Dinophysis caudata, in Uruguay (M endez & Ferrari 2002) and Argentina (Sar et al 2010).…”
Section: Distribution and Abundances Of Dinophysis Sppmentioning
confidence: 99%
“…Dinophysis spp. produce lipophilic toxin that, upon accumulation in bivalve mollusks, can cause diarrhetic shellfish poisoning in human consumers (Reguera et al 2014), and they have been recently reported in various shellfish farms of the Santa Catarina coast (Proença et al 2007(Proença et al , 2011.…”
Section: Introductionmentioning
confidence: 99%